The PAI‐1 4G/5G and ACE I/D Polymorphisms and Risk of Recurrent Pregnancy Loss: A Case–Control Study. (31st July 2014) - Kim, Jin Ju; Choi, Young Min; Lee, Sung Ki; Yang, Kwang Moon; Paik, Eun Chan; Jeong, Hyeon Jeong; Jun, Jong Kwan; Han, Ae Ra; Hong, Min A
<x xml:space="preserve">Abstract</x> Problem Thrombophilia has been postulated to be a contributor to the pathophysiology of recurrent pregnancy loss (RPL). We investigated the role of the plasminogen activator inhibitor type 1 (PAI‐1) 4G/5G and angiotensin converting enzyme (ACE) I/D polymorphisms in Korean patients with RPL. Method of study Genotyping was performed using the TaqMan assay in 227 RPL patients and 304 controls. Results The genotype distributions of both polymorphisms in the RPL group did not differ from those of controls. Because the frequency of being homozygous for ACE D/D and the PAI‐I 4G/4G combination has been reported to be significantly higher in RPL patients, this was also analyzed. However, no significant difference was noted; 3.1% of RPL patients had both ACE D/D and PAI‐I 4G/4G, as did 4.9% of controls (P = 0.791). Conclusion The current study suggests that both polymorphisms, either alone or in combination, are not major determinants of the development of RPL in Korean women.